2014
DOI: 10.1111/jnc.12715
|View full text |Cite
|
Sign up to set email alerts
|

Function, therapeutic potential and cell biology of BACE proteases: current status and future prospects

Abstract: The β-site APP cleaving enzymes 1 and 2 (BACE1 and BACE2) were initially identified as transmembrane aspartyl proteases cleaving the amyloid precursor protein (APP). BACE1 is a major drug target for Alzheimer’s disease because BACE1-mediated cleavage of APP is the first step in the generation of the pathogenic amyloid-β peptides. BACE1, which is highly expressed in the nervous system, is also required for myelination by cleaving neuregulin 1. Several recent proteomic and in vivo studies usingBACE1-andBACE2-def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
276
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 289 publications
(281 citation statements)
references
References 216 publications
(526 reference statements)
4
276
0
1
Order By: Relevance
“…It is marked by the generation and deposition of small, neurotoxic Aβ peptides in form of oligomeric aggregates and finally plaques in the brain parenchyma and vasculature. The Aβ peptide results from the sequential proteolytic processing of the amyloid precursor protein (APP) by β‐ and γ‐secretases (Lichtenthaler et al ., 2011; Vassar et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…It is marked by the generation and deposition of small, neurotoxic Aβ peptides in form of oligomeric aggregates and finally plaques in the brain parenchyma and vasculature. The Aβ peptide results from the sequential proteolytic processing of the amyloid precursor protein (APP) by β‐ and γ‐secretases (Lichtenthaler et al ., 2011; Vassar et al ., 2014). …”
Section: Introductionmentioning
confidence: 99%
“…3,4 The latter mainly consist of aggregated Ab peptides, which are generated from the amyloid precursor protein (APP) in a proteolytic cascade. 5 Once considered the evil moiety, amyloid plaques are now rather seen as inert deposits. Instead, oligomeric assemblies of Ab have been identified as the neurotoxic substrate.…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…Sequential cleavage of APP by BACE1 and the g-secretase complex creates Ab moieties, which are prone to aggregation. 5 Competitively, a-secretase cleaves APP instead of BACE1 and directs proteolysis toward the non-amyloidogenic pathway with shorter metabolites. Interdependence with further APP-cleaving secretases, i.e.…”
Section: Role Of Bace1 In Admentioning
confidence: 99%
“…It has been observed that knock-out of BACE1 or administration of the BACE1 inhibitor dramatically decreases A␤ levels in the brain and attenuates behavioral and electrophysiological deficits in APP-transgenic mice (4 -6). Thus, extensive investigations have focused on the direct inhibition of BACE1 to reduce A␤ load in the AD brain; however, these studies have unfortunately not yet led to any efficacious therapy for AD patients due to the various physiological roles of BACE1 (7). Using alternative methods to inhibit BACE1 might be a preferable investigative approach.…”
mentioning
confidence: 99%